2009
DOI: 10.1200/jco.2009.27.15_suppl.e17002
|View full text |Cite
|
Sign up to set email alerts
|

Primary squamous cell carcinoma of the oral cavity at presentation in Pakistan

Abstract: e17002 Background: Squamous cell carcinoma of oral cavity (SCCOC) is characterized by marked geographical differences in frequency and site distribution. Pakistan is situated within the high risk zone on the global oral cancer map. However, no reliable data exists on oral cancer in this area. Our aim was to determine clinicopathological features and patterns at presentation of primary SCCOC in a comprehensive cancer centre in Pakistan. Methods: Demographic, risk factors, pathological and AJCC staging data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…This is consistent with the findings of the study by Jamshed et al who also stated that well differentiated SCC was predominantly observed in OSCC affected patients. [7,14] A similar observation is also noted in the study by Rahman SS et al, who reports that majority of the patients had well differentiated carcinoma (70.73%). [10] In contrary, studies by Minhas et al [7],as well as Abdulla et al [13] reports most patients with moderately differentiated OSCC followed by well differentiated OSCC.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is consistent with the findings of the study by Jamshed et al who also stated that well differentiated SCC was predominantly observed in OSCC affected patients. [7,14] A similar observation is also noted in the study by Rahman SS et al, who reports that majority of the patients had well differentiated carcinoma (70.73%). [10] In contrary, studies by Minhas et al [7],as well as Abdulla et al [13] reports most patients with moderately differentiated OSCC followed by well differentiated OSCC.…”
Section: Discussionsupporting
confidence: 81%
“…[7,14] A similar observation is also noted in the study by Rahman SS et al, who reports that majority of the patients had well differentiated carcinoma (70.73%). [10] In contrary, studies by Minhas et al [7],as well as Abdulla et al [13] reports most patients with moderately differentiated OSCC followed by well differentiated OSCC. The delay in diagnosis is largely due to lack of awareness among the patients, who resort to home remedies before seeking professional help.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation